Generic and special constructions of pure O‐sequences. (27th June 2014) - Constantinescu, Alexandru; Kahle, Thomas; Varbaro, Matteo
Abstract : It is shown that theh ‐vectors of Stanley–Reisner rings of three classes of matroids are pure O ‐sequences. The classes are (a) matroids that are truncations of matroids, or more generally of Cohen–Macaulay complexes, (b) matroids whose dual is( rank + 2 ) ‐partite, and (c) matroids of Cohen–Macaulay type at most 5. Consequences for the computational search for a counterexample to a conjecture of Stanley are discussed.